Planning Parking Building Using Flat Slab And Drop Panel As A Replacement Conventional Beam With Analyzing Bending Moment Value & Sliding Style Based On SNI 1726-2012 - Munthe, Agyanata Tua; Jatmiko, Guntur (Journal of World Conference (JWC), 2020)
The construction of a 5-stored parking building is planned to use a flat slab (with drop panels). Flat slab (with drop panel) is a type of two-way plate without beams that directly rests on the column. the flat slab can reduce the height of the structure and construction time. However, flat slabs require plates that are thicker than usual to overcome deflection and punching shears. In this final project, a 5-story reinforced concrete structure will be reviewed with a span of 8 x 8.3 m. Analysis and design was carried out with the help of the 2016 ETABS program to find the value of intersection between floors, shear moments and forces taking into account the consequences of dead load, super dead load, life, and earthquake (dynamic)